A política bilíngue e as práticas docentes para a aquisição das línguas do surdo no ensino fundamental I - Fernandes, Francyllayans Karla da Silva (2021)
This research analyzes the conceptual and practical conditions of effectiveness of bilingual policies for the deaf included in regular school. These national educational policies determine the inclusion of differences in regular school, among them the deaf student who needs to have his language as a mediating tool in the process of teaching and learning. However, sign language is not effectively part of the regular school, because the inclusive school is mostly composed of listeners who use oral language and have another culture. Thus, the deaf experience linguistic isolation and the erasure of their identity, so it is essential to discuss the scenario of text production and practice of inclusive and bilingual educational policies. In this context, it is in the analysis between what is said and what is done that one understands the reality of the inclusion of the deaf and their language in regular school. Even with the strengthening of the struggle for the recognition of linguistic difference and identity of the deaf, he remains isolated in his language, as if Libras still occupied a strange and unknown place. The Laws No. 10.436 of 2002 and No. 10.098 of 2000, as well as Decree No. 5626 of 2005, enabled the recognition of the importance of sign language for the deaf, as well as their linguistic, cultural and identity differences coined by the socioanthropological view of deafness. However, there are still gaps in the use of Libras as L1 in educational practice and in the constitution of the bilingual environment within the legal and inclusive perspective in regular school. In these terms, the objective of this research is to analyze the implementation of bilingual education policy for the deaf in inclusive school in Canguaretama-RN. For this, we highlight the Libras as a language and means of expression, communication and cultural belonging of a people, so it is constitutive of the deaf person's life, including their school learning process, even if it does not determine the effectiveness of an inclusive bilingual process. From this perspective, the research is a case study that follows the qualitative methodology approach using interviews and non-participant observation to collect data. The research took place in a public school in the municipality of Canguaretama-RN and was composed of two Elementary I teachers, one from the 2nd and the other from the 3rd grade, the school coordinator and the school manager. Both teachers have a deaf student included in their classroom. Through data collected in interviews and observations, it was possible to verify that the indications of bilingual policy are not being effective in inclusive school, because deaf children are subjected to listener methodology with the teaching of L2 before the acquisition of L1, making it impossible communicative relations, since the school has no interpreter of Libras and teachers, coordinator and manager have no training in sign language or deaf education. Thus, deaf children are immersed in a segregationist process, since they are included, but isolated.